TOPIC: STAGES OF CONDUCTING THE BBB METHOD ON THE TOPIC OF WHAT THE ECONOMIC AND SOCIAL GEOGRAPHY OF UZBEKISTAN STUDIES (Academicia Globe: Inderscience Research, 2022)
This article is about the transfer of the BBB method to students on the topic of what the economic and social geography of Uzbekistan studies and strengthening their knowledge on this topic.